Expected costs and benefits of genetic counselling and germline genetic testing in metastatic prostate cancer - Michiel Vlaming; Lambertus A. L. M. Kiemeney; Wouter Koole; Inge M. van Oort; Eveline M. A. Bleiker; Margreet G. E. M. Ausems; Geert W. J. Frederix (Human Genetics, 2026)
Identifying pathogenic germline variants in men with metastatic prostate cancer is important for therapeutic options and for identifying relatives who may have a high cancer risk. To keep genetic testing costs manageable, it is important to identify which patients should be selected for testing. In this study, we compared expected costs and number of identified pathogenic variants in two scenarios: offering genetic testing to all men with metastatic prostate cancer versus testing only those with additional risk factors linked to a higher likelihood of carrying a pathogenic variant. Costs were evaluated with a mainstream genetic testing pathway, where testing is discussed by a non-genetic healthcare professional. Using Dutch national incidence data, predefined healthcare cost frameworks, and a hypothetical assumption for the acceptance rate of patients, we modelled total costs for the Netherlands and number of identified pathogenic variants for each approach. The costs of genetic testing and post-test counselling decreased threefold when applying selection criteria, compared to the scenario where all metastatic prostate cancer patients are eligible. However, applying selection criteria would result in missing 41% clinically relevant pathogenic germline variants that would otherwise be identified. This implies that, at national level, a discussion should be started regarding willingness to pay for identifying pathogenic germline variants.